PENGARUH VARIABEL MAKRO TERHADAP NILAI AKTIVA BERSIH (NAB) REKSADANA SAHAM SYARIAH - Yeny Fitriyani; Mariana Ratih Ratnani; Natiq Al Aksar (Wahana Islamika: Jurnal Studi Keislaman, 2020)
This study aims to analyze the effect of macro variables (Islamic Indonesian bank certificates, inflation rates, rupiah exchange rates, the amount of money in circulation, and the composite stock price index) on the net asset value (NAV) of Islamic stock mutual funds. The population in this study consisted of five Sharia stock mutual fund products with the most complete total NAV, namely Trim Syariah Shares, CIMB-Principal Islamic Equity Growth Sharia, Mandiri Investa Syariah Attractive, Cipta Syariah Equity, and Manulife Syariah Sectoral Amanah during 2013 to 2016. Analysis tools The panel data analysis method of Fixed Effect (FEM) is used. The results showed that the inflation rate, the exchange rate of the rupiah, the Jakarta Composite Index (JCI) and the money supply significantly influenced the NAV of Islamic mutual fund shares. The variable that has no significant effect on the NAV of Islamic mutual funds is SBIS.